Where should i publish my next manuscript on limnology? - Neiff, Juan Jose (2016)
When we need to spread the limnological knowledge, arises an issue that is not less than: where to publish our next article? In recent decades, the main element of evaluation are the “papers” and the sentence “publish or perish” haunts many scientists. It is imperative that researchers to share their discoveries or new knowledge. The dilemma arises because the scientific agencies (led by scientists) have installed what I call prestige system in which researchers needs a number of articles published in mainstream journals with highest positions in the ranking to progress in their scientific carrier. This determines a strong pressure on the subjects under investigation, in the allocation of resources and, sometimes, comes to desperation to publish. It is also producing the neglect of regional issues hardly find place in those journals and end up published in journals unreliable. The dissemination of the limnological topics in Latin American journals gradually lost prominence. In my opinion, it´s necesary to spread the results for the people that paying our salaries and supports our projects. Put another way, publish in good local journals, without prejudice to also publish in journals of high international ranking. Scientific production should be evaluated for their trascendence, by his transforming power and not just by impact factors used today by many agencies.